NONLINEAR FREQUENCY SPECTRAL ANALYSIS OF CRACKED ROTOR BASED ON NOFRF - WU HongXia; HAN Jie; CHEN Hong; QIN DongChen (Jixie qiangdu)
The nonlinear approximation model of cracked rotor,to explain the nonlinear phenomena,is constructed. The nonlinear output frequency response function（ NOFRF） and the theory of nonlinear frequency spectral analysis are illustrated.Based on this theory,the simulation analysis of cracked rotor is accomplished. The analysis provides insight into how new frequency generates. Additionally,the nonlinear phenomena of cracked rotor,including the generation of super-harmonic components and sub-resonances are explained. Experimental result shows that the higher order NOFRF is sensitive to the racked rotor with cracks of different depth. This research study establishes an important theory basis for accurate fault diagnosis of cracked rotor.